Banker Algorithm Simulation Software - Cerlinto Hutagalung (Cattleya Darmaya Fortuna, 2020)
Banker's algorithm is an algorithm that models a bank in a small town dealing with a set of customers. This banker algorithm is used to deal with queuing problems in banking. In this case, one of them is how to simulate queues in banking. In this study, the design and manufacture of simulation software is used to help simulate whether a system is in a safe state or an unsafe state, in a safe condition the process is continued but if the process is unsafe the process is delayed until the system is in a safe state. The result of this research is a banker algorithm simulation software that models a banker who is dealing with a group of customers in a bank.